2003
DOI: 10.1074/jbc.m301619200
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac Sulfide Is a Noncompetitive γ-Secretase Inhibitor That Preferentially Reduces Aβ42 Generation

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) have been known to reduce risk for Alzheimer's disease. In addition to the anti-inflammatory effects of NSAIDs to block cylooxygenase, it has been shown recently that a subset of NSAIDs selectively inhibits the secretion of highly amyloidogenic A␤42 from cultured cells, although the molecular target(s) of NSAIDs in reducing the activity of ␥-secretase for A␤42 generation (␥ 42 -secretase) still remain unknown. Here we show that sulindac sulfide (SSide) directly act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
189
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 46 publications
18
189
2
Order By: Relevance
“…2 Treatment of amyloid precursor protein transgenic mice with some NSAIDs suppressed the development of amyloid plaques pathology 32 and NSAIDs lowered the level of amyloid b-protein in cultured cells. 5 Although it was recently reported that some NSAIDs inhibit g-secretase that is involved in amyloid b-protein production, 33 the mechanism for decrease in amyloid b-protein production by NSAIDs is not fully understood. We showed that induction of GRP78 and CHOP by indomethacin was not specifically observed in gastric mucosal cells but observed in other cells, such as HEK293 (human embryonic kidney) cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2 Treatment of amyloid precursor protein transgenic mice with some NSAIDs suppressed the development of amyloid plaques pathology 32 and NSAIDs lowered the level of amyloid b-protein in cultured cells. 5 Although it was recently reported that some NSAIDs inhibit g-secretase that is involved in amyloid b-protein production, 33 the mechanism for decrease in amyloid b-protein production by NSAIDs is not fully understood. We showed that induction of GRP78 and CHOP by indomethacin was not specifically observed in gastric mucosal cells but observed in other cells, such as HEK293 (human embryonic kidney) cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the first of these three mechanisms, high dose ibuprofen (100-500 mM) has been shown to reduce Ab42 production in vitro, an effect also shown by other NSAIDs to be independent of their antiinflammatory effects on regulating COX, PPAR, and NFkB (Weggen et al, 2001;Morihara et al, 2002;Sagi et al, 2003;Takahashi et al, 2003). Although the COX-dependency of ibuprofen's effects on Ab42 suppression has not been tested, another NSAID sulindac has been more extensively analyzed and clearly reduces Ab42 independent of COX (Weggen et al, 2001;Sagi et al, 2003;Takahashi et al, 2003). Ab42 production was reduced in 3-month-old Tg2576 mice with a brain ibuprofen level of B2 mM, which, surprisingly, was much lower than dosing required in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The major inflammatory target of NSAIDs, including ibuprofen, is cyclooxygenase (COX), and in our model ibuprofen-induced plaque reduction was associated with reductions in brain interleukin-1b, a downstream target of COX. Although this and other evidence suggests a possible role of inflammation in controlling plaque pathogenesis, this hypothesis has been challenged by discovery of an unexpected COX-independent function of a subset of NSAIDs (including ibuprofen) in reducing Ab42 production in vitro (Weggen et al, 2001(Weggen et al, , 2003aMorihara et al, 2002;Eriksen et al, 2003;Sagi et al, 2003;Takahashi et al, 2003;Zhou et al, 2003). Adding to the controversy whether the mechanism(s) of plaque reduction are inflammationdependent or -independent, it is unclear whether the high ibuprofen concentrations required in vitro to reduce Ab42 production can be attained in the human brain with doses shown epidemiologically to reduce AD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a subset of NSAIDs such as Ibu, sulindac sulfide (SSide), indomethacin (Ind) (Weggen et al, 2001) and flurbiprofen (Flu) selectively decreased the secretion of Aß(1-42) from cultured cells independently of cyclooxygenase (COX) activity and lowered the amount of soluble in the brains of Tg2576 mouse. Third, SSide and enantiomers of Flu have been reported to target γ-secretase and preferentially reduce Aß(1-42) generation (Takahashi et al, 2003;Eriksen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%